Exogenous Melatonin Application Delays Senescence of Kiwifruit Leaves by Regulating the Antioxidant Capacity and Biosynthesis of Flavonoids - Liang, Dong; Shen, Yanqiu; Ni, Zhiyou; Wang, Qin; Lei, Zhi; Xu, Nengqin; Deng, Qunxian; Lin, Lijin; Wang, Jin; Lv, Xiulan; Xia, Hui (Frontiers in Plant Science, 2018)
Melatonin, a multiple signal molecule, plays important roles in delaying senescence during the development of plants. Because few species have been studied for the effect of exogenous melatonin on anti-aging, the plausible mechanism of melatonin of anti-aging effects on other plant species has remained largely unknown. In the present study, the effects of exogenous melatonin on leaf senescence in kiwifruit were examined during natural aging after melatonin (200 μM) or water (Control) pretreatment. The decreased membrane damage and lower hydrogen peroxide (H2O2) content due to the enhanced scavenging activity of antioxidant enzymes peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) demonstrated that melatonin effectively delayed the aging of kiwifruit leaves. Likewise, owing to up-regulated expression of chlorophyll a/b-binding protein (CAB) gene in the sampled leaves pretreated with melatonin, chlorophyll degradation decreased. Therefore, osmoregulatory substances in sampled leaves accumulated (e.g., soluble sugar and soluble protein) and seedling cell environment stability was maintained. Simultaneously, melatonin decreased H2O2 concentration owing to increased glutathione (GSH) and ascorbate (AsA) content, and the expression levels of glutathione reductase (GR), ascorbate peroxidase (APX), monodehydroascorbate reductase (MDAR), dehydroascorbate reductase (DHAR) were up-regulated by melatonin application, indicating that the increase of GSH and AsA was attributed to the expression of these genes. In addition, a large amount of flavonoids accumulated in seedlings pretreated with melatonin, and transcript levels of eight genes involved in flavonoid synthesis, including phenylalanine ammonia-lyase (PAL), cinnamate-4-hydroxymate (C4H), chalcone synthase (CHS), flavanone 3-hydroxylase (F3H), flavonol synthase (FNS), leucoanthocyanin reductase (LAR), anthocyanin reductase (ANR), flavonoid 3-O-glucosyltransferase (UFGT) were enhanced in response to melatonin application. These results indicated that melatonin delayed aging of kiwifruit leaves by activating the antioxidant capacity and enhancing flavonoid biosynthesis. All of these results can provide clear proof that melatonin plays a key roles in delaying leaf senescence.